Effectiveness of adding ZnO thin films to metamaterial structures as sensors - Saktioto Saktioto; Yan Soerbakti; Ari Sulistyo Rini; Budi Astuti; Erman Taer; Rahmondia Nanda Setiadi; Syamsudhuha Syamsudhuha; Sofia Anita; Yolanda Rati (Indonesian Physics Communication, 2024)
Metamaterials are artificial materials with the characteristics of a negative refractive index and high resonance sensitivity. Advanced engineering in metamaterials can realize great potential in combination with zinc oxide (ZnO) semiconductor materials, which can increase the efficiency of sensor technology compared to other conventional material models. This research aims to investigate the optical properties and develop an invention for a hybrid sensor media based on a split ring resonator (SRR) metamaterial structure integrated with a thin layer of ZnO. The research methodology was carried out by simulation by designing and characterizing SRR metamaterials which were designed with variations in SRR patterns, geometry, substrate materials, unit cell configurations, and variations in the thickness of the ZnO thin layer. Geometry characterization of SRR metamaterials was carried out using the Nicolson-Ross-Weir electromagnetic (EM) field function approach, specifically the optical parameters permittivity, permeability, and refractive index. They are optimizing the performance of hybrid sensor components based on metamaterials and ZnO thin films using the GHz scale EM field function approach, especially in the reflection, transmission, and absorption spectrum. Analysis of metamaterial characteristics identifies the optical properties of permittivity, permeability, and negative refractive index which are increased and optimized from the thin layer integration model 200 nm thick ZnO in the SRR metamaterial structure with a 3×3 square pattern configuration at a resonance frequency of 1.889 GHz. The performance of the hybrid sensor media provides a resonant frequency of three equal bandwidths in the frequency range 2.89 – 3.52, 5.28 – 6.54, and 7.57 – 8.46 GHz. In addition, the highest absorption spectrum of 73% is at a frequency of ~8 GHz.